Interspecific hybrids Allium as a genetic source of increasing the bioresource collection - V. S. Romanov (Овощи России)
Purpose. To obtain and evaluate breeding forms of interspecific allium hybrids based on econom- ically useful characteristics and resistance to downy mildew to replenish the bioresource collection of the genus Allium L.Material and Methods. The studies were carried out on plants of progeny I1-5 from BC1 interspecif- ic allium hybrids of crossing combinations F5 (A. cepa × A. vavilovii) and F5 (A. cepa × A. fistulosum). Morphological assessment was carried out according to the signs of the bulb. Plants in the field were grown using the technology of onion cultivation for this soil and climatic zone. The phytopathological assessment included identifying the nature of onion plants resistance to downy mildew.Results. In a combination of crossing species of A. cepa × A. fistulosum and A. cepa × A. vavilovii, the plants formed bulbs weighing 54.4-100.0 g. The maximum bulb weight is more than 85.0 g in plants, I5BC1(F5(A. cepa × A. vavilovii)). Onion plants mainly showed splitting into yellow and red bulbs. Among the crossing combinations species of A. cepa × A. fistulosum and A. cepa × A. vavilovii, the red coloration of the bulb ranged from 44.0 to 97.0%. In the combination species of A. cepa × A. fistulosum, the broadly elliptical bulb shape prevailed (15-85%). In a combination species crossing of A. cepa × A. vavlovii, plants I3BC1(F5(A. cepa × A. vavilovii)) 95.0% formed elliptical bulbs, and 5.0% formed round bulbs. In plants of the crossing combination species A. cepa × A. fistulosum, the number of plants resistant to downy mildew varied in inbred generations from 42.0 to 49.0%. In combination with the crossing species of A. cepa × A. vavilovii, with an increase in the inbred generation from I1 to I5, the number of plants resistant to downy mildew increased from 50.0 to 74.0%. In the control, 90.0% of unstable plants were noted, as well as their death.Conclusion. The analysis of plants of interspecific allium hybrids from inbred progeny of I1-5 combinations of crosses species of A. cepa × A. vavilovii and A. cepa × A. fistulosum showed the pos- sibility of increasing onion biological resources due to interspecific hybridization, saturating crosses and inbreeding of breeding forms. A morphological assessment of the qualitative and quantitative characteristics of the onion plants obtained made it possible to identify promising breeding forms from the progeny of I3BC1(F5(A. cepa × A. fistulosum)) the weight of the bulb is about 100.0 g of elliptical and broadly elliptical shape. Based on a phytopathological assessment, recombinant Allium forms as a genetic source were isolated in the progeny of I5BC1(F5(A. cepa × A. vavilovii)) with 74.0% of plants resistant to downy mildew.